The Application of the Puzzle-Based Syllable Method to Improve Early Reading Skills in Elementary School Students: A Study in Islamic Elementary Education - Naman, Nasra; Nursyamsi, Nursyamsi (Journal of Indonesian Islamic Studies, 2025)
Early reading instruction is a foundational component of literacy development in elementary education, particularly within Islamic schooling contexts where cognitive skills are nurtured alongside moral and spiritual values. However, challenges such as limited engaging media and low student motivation often impede reading acquisition. This study aims to examine: (1) teacher and student activities in implementing a puzzle-based syllabic method, and (2) improvements in early reading skills among first-grade students at State Elementary School 435 Sanggalangi’. The study employed Classroom Action Research consisting of two cycles—planning, action, observation, and reflection—with a total of 19 students. Data were collected through observation, tests, and documentation, and analyzed using qualitative and quantitative descriptive techniques. The results show that the use of interactive puzzle media enhanced teacher performance and increased student participation in syllable assembly and sentence formation. Early reading skills improved significantly, with mastery rising from 57.89% in Cycle I to 89.47% in Cycle II. The integration of an engaging puzzle-based syllabic method, aligned with Islamic educational principles such as tarbiyah-oriented guidance and value-based learning, proved effective in stimulating students’ cognitive abilities, interest, and active involvement. This study contributes to the development of innovative, enjoyable, and value-integrated literacy instruction within Islamic elementary education.